Cortical Network Synchrony Under Applied Electrical Field in vitro - Tang-Schomer, Min D.; Jackvony, Taylor; Santaniello, Sabato (Frontiers in Neuroscience, 2018)
Synchronous network activity plays a crucial role in complex brain functions. Stimulating the nerv-ous system with applied electric field (EF) is a common tool for probing network responses. We used a gold wire-embedded silk protein film-based interface culture to investigate the effects of ap-plied electric fields (EF) on random cortical networks of in vitro cultures. Two-week-old cultures were exposed to EF of 27 mV/mm for <1 hour and monitored by time-lapse calcium imaging. Net-work activity was represented by calcium signal time series mapped to source neurons and analyzed by using a community detection algorithm. Cortical cultures exhibited large scale, synchronized oscillations under alternating EF of changing frequencies. Field polarity and frequency change were both found to be necessary for network synchrony, as monophasic pulses of similar frequency changes or EF of a constant frequency failed to induce correlated activities of neurons. Group-specific oscillatory patterns were entrained by network-level synchronous oscillations when the alternating EF frequency was increased from 0.2 Hz to 200 kHz. Binary responses of either activity increase or decrease contributed to the opposite phase patterns of different sub-populations. Conversely, when the EF frequency decreased over the same range span, more complex behavior emerged showing group-specific amplitude and phase patterns. Based on the findings from this pi-lot study, we hypothesized a mechanism of network control by temporal coordination of distributed neuronal activity, involving coordinated stimulation by alternating EF polarity, and timed delay by change of frequency. These insights will inform the design of future neuromodulation approaches for controlling neural network functions.